Delineating Quality Indicators of Inpatient Psychiatric Hospitalization. (September 2022) - Delaney, Kathleen R.; Loucks, Jeannine; Ray, Richard; Blair, Ellen W.; Nadler-Moodie, Marlene; Batscha, Catherine; Sharp, David M.; Milliken, Dani
Background: Assuring quality care is critical to the well-being and recovery of individuals receiving inpatient psychiatric treatment, yet a comprehensive map of quality inpatient care does not exist. Aims: To isolate and describe quality elements of inpatient psychiatric treatment. Methods: A survey queried psychiatric inpatient nursing leaders on what they considered to be critical elements of quality. The survey was emailed to 40 American Psychiatric Nurses Association members, and 39 individuals responded. In the survey, participants were asked to comment on the importance of six dimensions of quality as well as quality indicators used on their units. Results: Data from this survey indicate how thought leaders conceptualized quality of inpatient care. A unifying philosophy of care was endorsed as a quality element as was structure that affords staff available time on the unit—engaging with patients. While staffing levels were viewed as important, the respondents commented on the nuances between staffing and quality. Participants endorsed the importance of involving individuals in their treatment planning as well as tapping into patients' perspectives on the treatment experience. Conclusions: The participants' responses compliment the quality literature and reinforce the need to develop a comprehensive map of quality elements. These elements interact in complex way, for instance, staffing, engagement, and teamwork is tied to the organizational structure and philosophy of care, which in turn facilitates consumer involvement in care. Thus, gauging the impact of quality on outcomes will demand consideration of the interaction of factors not just the linear relationship of one element to an outcome.